The Impact of Social Media Towards Brand Equity: An Empirical Study of Mall X - Lavina Tresna; Jovita Christin Wijaya (iBuss Management, 2015)
This research is aimed to analyze the impact of social media use and functionalities towards brand equity with an empirical study of Mall X. Mall X’s Instagram is being analyzed throughout this research. Furthermore, this research attempts to examine the impact of social media use and functionalities on brand equity elements simultaneously and individually. Data processing methods used in this research are validity and reliability test and classical assumption tests, while simple and multiple linear regressions are used as data analysis methods. Online questionnaire is used to collect data of 111 respondents. These research findings show that identity and conversation use and functionalities have significant impact on brand awareness simultaneously and individually, sharing and presence use and functionalities have significant impact on brand associations simultaneously and individually, reputation use and functionality has significant impact on perceived quality, and relationship use and functionality has significant impact on brand loyalty.Keywords: Social Media, Brand Awareness, Brand Association, Perceived Quality, Brand Loyalty